The Role of Pension Fund Insurance on Waqf - Alfin Agung Azhar; Tri indah Fadhila Rahnma (Journal of Indonesian Management, 2022)
Waqf Pension fund insurance is a waqf in the form of a sharia insurance policy, in which the investment value and or insurance benefits are represented by the main insured. Of course with the knowledge of the heirs. This journal uses data collection techniques by means of observation, and documentary methods. Furthermore, when the data needed has been obtained through data from previous theoretical studies and observations have been collected. Next, conduct an analysis to produce a factual conclusion and can be applied by the community. Data analysis uses the analysis of relative thinking, which is a combination of deductive and inductive thinking. The inductive method is discussing problems obtained through specific facts. Then, conclusions that have a general nature are obtained. While deductive is a method of examining a problem through its general nature to more specific or specific Waqf Pension fund insurance is a waqf in the form of a sharia insurance policy, in which the investment value and or insurance benefits are represented by the main insured. Of course with the knowledge of the heirs. The benefits of pension funds, apart from being an old-age guarantee, can also be used as a value for worship, which can improve the welfare of the community and advance the value of the national economy through waqf. Along with the growth of the people who follow them as pension fund insurance customers, participating in the role of national waqf is growing rapidly